Snakin-1 affects reactive oxygen species and ascorbic acid levels and hormone balance in potato - Nahirñak, Vanesa; Rivarola, Maximo Lisandro; Almasia, Natalia Ines; Barrios Baron, María Pilar; Hopp, Horacio Esteban; Vile, Denis; Paniego, Norma Beatriz; Vazquez Rovere, Cecilia (PLOS, 2019)
Snakin-1 is a member of the Solanum tuberosum Snakin/GASA family. We previously demonstrated that Snakin-1 is involved in plant defense to pathogens as well as in plant growth and development, but its mechanism of action has not been completely elucidated yet. Here, we showed that leaves of Snakin-1 silenced potato transgenic plants exhibited increased levels of reactive oxygen species and significantly reduced content of ascorbic acid. Furthermore, Snakin-1 silencing enhanced salicylic acid content in accordance with an increased expression of SA-inducible PRs genes. Interestingly, gibberellic acid levels were also enhanced and transcriptome analysis revealed that a large number of genes related to sterol biosynthesis were downregulated in these silenced lines. Moreover, we demonstrated that Snakin-1 directly interacts with StDIM/DWF1, an enzyme involved in plant sterols biosynthesis. Additionally, the analysis of the expression pattern of PStSN1::GUS in potato showed that Snakin-1 is present mainly in young tissues associated with active growth and cell division zones. Our comprehensive analysis of Snakin-1 silenced lines demonstrated for the first time in potato that Snakin-1 plays a role in redox balance and participates in a complex crosstalk among different hormones.